Chemical characterization and biotechnological potential of Salvia rosmarinus Spenn essential oil nanoemulsions - Chaves, Karen Caroline Cantanhede (2024)
This study aimed to determine the total phenolic compounds, evaluate the antioxidant and anti-inflammatory activities of nanoemulsions (O/W) and essential oils (EOs) from Salvia rosmarinus (rosemary). The plant material was obtained in the city of São Luís (MA). The EO was obtained by the hydrodistillation technique in a modified Clevenger extractor and the NOE's by phase inversion. The chemical constituents of EO were determined by GC-MS. The determination of total phenolic compounds (TPC) was performed by the Folin-Ciocalteu method. The anti-inflammatory activity was performed by the method of protein denaturation and the antioxidant activity by the spectrophotometric method of scavenging hydroxyl radicals. The GC-MS allowed quantifying 1,8-cineol (30.22%), α-pinene (22.14%), camphor (18.33%) and camphene (10.36%) as major components of the EO. The TPC of the EO was quantified at 26.74 mg EAT g-1 and the refractive index at 1.466 nD 25°. In the antioxidant activity test, an EC50 of 80.33 mgL-1 was obtained for the EO and from 19.56 to 408.85 mg L-1 for the nanoemulsions. In the anti-inflammatory activity assay, an EC50 of 62.46 mgL-1 was obtained for EO and 64.96 to 4220.25 mg L-1 for NOE's. Finally, the pharmacological activities tested showed efficient values ​​for EC50, therefore considered active. This activity is attributed to its chemical compounds present, thus encouraging studies with this species aiming at its potential application in a formulated bioproduct.